Representation rings of extensions of Hopf algebra of Kac-Paljutkin type - Dong Su; Shilin Yang (Electronic Research Archive)
In this paper, we focus on studying two classes of finite dimensional $ Δ $-associative algebras, which are extensions of a family of $ 2n^2 $-dimensional Kac-Paljutkin type semi-simple Hopf algebras $ H_{2n^2} $. All their indecomposable modules are classified. Furthermore, their representation rings are described by generators with suitable relations.